2008
DOI: 10.3892/or.19.5.1191
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the key proteins and pathways involved in the metastasis of colorectal carcinoma

Abstract: Abstract. Metastasis-associated genomic alterations have been recognized to play a critical role in tumor metastasis. Primary and metastatic tumor cells in mice and tumors in a patient were studied by cDNA array analysis. Selected genes were determined by RT-PCR and immunohistochemistry. Pathways on changed genes were statistically analyzed. The function of Grb2 was determined by in vitro wound assay. Nodal metastatic cells had a stronger ability of growth and metastasis than primary tumor cells. A total of 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…A high frequency of up-regulation of Grb2 and HER2 expression in metastases primary gastric tumors and downregulation of them in primary gastric tumors suggests that Grb2 and HER2 play critical roles in human gastric tumorigenesis and metastasis. This notion is clearly supported by our previous study in colorectal cancer showing that Grb2 and genes in the Grb2-mediated pathways was signiWcantly elevated in the metastases and blocking the Grb2-SH2 domain signaling transduction could inhibit cell motility (Yu et al 2008).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A high frequency of up-regulation of Grb2 and HER2 expression in metastases primary gastric tumors and downregulation of them in primary gastric tumors suggests that Grb2 and HER2 play critical roles in human gastric tumorigenesis and metastasis. This notion is clearly supported by our previous study in colorectal cancer showing that Grb2 and genes in the Grb2-mediated pathways was signiWcantly elevated in the metastases and blocking the Grb2-SH2 domain signaling transduction could inhibit cell motility (Yu et al 2008).…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, authors have reported overexpression of Grb2 in breast cancer in conjunction with overexpression of SHP-1 (Yip et al 2000); this combined overexpression enhanced downstream signaling through the extracellular signal-related kinase kinase/mitogen-activated protein kinase pathway. Our laboratory once detected Grb2 expression in 35 colorectal cancer specimens through immunohistochemistry of tissue microarray and found that Grb2 was signiWcantly elevated in the metastases (Yu et al 2008). Cheng et al (1998 stressed the importance of Grb2 gene dosage in the onset and development of mammary carcinoma as a possible signal ampliWcation mechanism downstream of active RTKs.…”
Section: Introductionmentioning
confidence: 96%
“…GRB2 is critical for cell cycle progression and angiogenesis 45. Blocking the GRB2 signalling inhibits CRC cell motility 46. POSTN has been found to be highly upregulated in CRC tissues and sera of CRC patients 47.…”
Section: Discussionmentioning
confidence: 99%
“…High-expression of GRB2 could promote malignant transformation and progression, and correlate with poor prognosis in several human cancers, such as breast, bladder, gastric and colorectal cancers, suggesting that GRB2 is a potential target for cancer therapy [24][25][26][27]. Moreover, the molecules and signaling pathways that regulate cell proliferation and survival are receiving considerable attention as potential targets for anticancer strategies [28,29].…”
Section: Discussionmentioning
confidence: 99%